EFEKTIVITAS PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) DALAM PEMBERDAYAAN EKONOMI MASYARAKAT DI KAMPUNG LONG SULUI KECAMATAN KELAY KABUPATEN BERAU: EFEKTIVITAS PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) DALAM PEMBERDAYAAN EKONOMI MASYARAKAT DI KAMPUNG LONG SULUI KECAMATAN KELAY KABUPATEN BERAU - Syaprudin Syaprudin (ECO-BUILD, 2025)
The purpose of this study was to determine and analyze the effectiveness of the Achievement Orchid PKBM in community economic empowerment in Long Sului Village, Kelay District, Berau Regency. Primary data were collected through questionnaires which were distributed to 88 respondents who were used as research samples. The analytical tools used are: validity test, reliability test, mean (calculated average), standard deviation (standard deviation), and average percentage. The results of this study indicate that: 1) Assessment of the effectiveness of the Achievement Orchid PKBM in empowering the economy of the Long Sului Village community through several indicators, namely: a) Human resource development has a mean value of 4.35 with a standard deviation of 0.59; b) Group institutional development has a mean value of 4.27 with a standard deviation of 0.54; c) Public (private) capital fertilization has a mean value of 4.34 with a standard deviation of 0.57; d) Productive business development has a mean value of 4.27 with a standard deviation of 0.60; e) Provision of appropriate information has a mean value of 4.19 with a standard deviation of 0.54. 2) PKBM Orchid Achievement in the economic empowerment of the Long Sului Village community can be categorized as effective, based on the average answer of most respondents in agreeing answers, which is 60.23%, which is included in the effective category (56% - 75%). Thus it was decided to reject the hypothesis in this study.